Hepatic Cirrhosis: A Literature Review - Dewi, Komang Puspa; Abida, Aisya Nur; Aswandani, Alifa; Anggraeni, Baiq Annisa Ulfi; Shofa, Dhiya Atsila; Aunurrahman, Muhammad Rezky Audia; Husna, Najla Firyal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Hepatic cirrhosis is a chronic liver disease characterized by fibrosis and regeneration of nodules in the liver, which if it occurs for a long time, hepatocyte cells will be damaged so that they cannot function again, potentially threatening life. The prevalence of incidence and mortality depends on the progression of hepatic cirrhosis, which is influenced by the patient's etiology and treatment. The purpose of writing this article is to provide new insight into the importance of understanding the risk factor and causes of hepatic cirrhosis. This study uses a literature review approach by collecting data from online databases including Google Scholar, ProQuest, MDPI, and PubMed to search for articles discussing “Hepatic Cirrhosis”. Early detection based on clinical manifestations and appropriate treatment can reduce mortality and prevent complications that may worsen the patients condition.